Increasing halal value chain awareness: training for food and beverage entrepreneurs - Heni Pratiwi; Lucky Enggrani Fitri; Yusuf Zaini Aprizal; Aditya Pratama; Muhammad Roihan (Journal of Saintech Transfer, 2025)
The Mandatory Halal October 2024 (WHO) Campaign is a strategic initiative implemented by the Halal Product Guarantee Agency (BPJPH) of the Ministry of Religious Affairs to accelerate Indonesia’s ambition to become a global halal center. This program supports the enforcement of mandatory halal certification regulations, covering food and beverage products, raw materials and additives, as well as slaughter products and services. Mendalo Indah Village, which hosts Jambi University, has approximately 19.5% of its population engaged in trading and entrepreneurial activities, particularly in the food and beverage sector, where halal certification remains limited. This community-based program aimed to improve awareness, readiness, and institutional support for halal certification among local Micro, Small, and Medium Enterprises (MSMEs). The program identified 25 MSMEs ready for halal certification and strengthened collaboration among government agencies, academic institutions, and business actors to support the implementation of the Mandatory Halal policy. Assistance in the Halal Product Process (PPH) was provided to facilitate applications for free halal certification in line with WHO targets. Key outputs included a Cooperation/License Agreement, enabling partners to sustainably utilize the program to support halal certification for food and beverage MSMEs. The initiative enhanced MSME empowerment and complemented previous support programs such as Business Identification Number (NIB) and Home Industry Food Permit (PIRT) facilitation, while local media publications supported broader dissemination of the WHO campaign.